1994
DOI: 10.1128/aac.38.8.1732
|View full text |Cite
|
Sign up to set email alerts
|

Role of efflux pump(s) in intrinsic resistance of Pseudomonas aeruginosa: resistance to tetracycline, chloramphenicol, and norfloxacin

Abstract: Most strains of Pseudomonas aeruginosa are significantly more resistant, even in the absence of R plasmids, to many antimicrobial agents, including P-lactams, tetracycline, chloramphenicol, and fluoroquinolones, than most other gram-negative rods. This broad-range resistance has so far been assumed to be mainly due to the low permeability of the P. aeruginosa outer membrane. The intrinsic-resistance phenotype becomes further enhanced in "intrinsically carbenicillin-resistant" isolates, which were often assumed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
269
1
6

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 361 publications
(286 citation statements)
references
References 47 publications
10
269
1
6
Order By: Relevance
“…Other heavy metal salts (analytical grade) were from commercial sources. The sources of antibiotics were as previously described (8,9). Carbonyl cyanide m-chlorophenylhydrazone (CCCP), disodium ATP, and sodium sulfadiazine were purchased from Sigma Chemical Co. (St. Louis, Mo.).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other heavy metal salts (analytical grade) were from commercial sources. The sources of antibiotics were as previously described (8,9). Carbonyl cyanide m-chlorophenylhydrazone (CCCP), disodium ATP, and sodium sulfadiazine were purchased from Sigma Chemical Co. (St. Louis, Mo.).…”
Section: Methodsmentioning
confidence: 99%
“…The OMs and cytoplasmic membranes (CMs) were prepared by sonic disruption followed by differential extraction with Sarkosyl (Sigma) (8). The protein composition was analyzed by sodium dodecyl sulfate-slab polyacrylamide (13%) gel electrophoresis (8).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(36,37) The MexAB system is able to pump antibiotics, organic dyes, detergents, and organic solvents from within a cell and can decrease bacterial susceptibility to several classes of antibiotics and TCS. (37,38) The genera Pseudomonas and Cupriavidus, along with other bacteria, are known to carry the mexB gene. (39,40) Results from Zhang et al, suggest that mexB is found on plasmids as well and may be mobile in the environment.…”
Section: Influence Of Tcc On Abundance Of Args and Inti1mentioning
confidence: 99%
“…Initially, intrinsic drug resistance was characterized as a passive mechanism associated with the absence of the drug target or lack of bacterial permeability (15,16), but recent studies have established that it can depend on drug efflux (46)(47)(48). Efflux pumps can contribute to acquired drug resistance due to overexpression (24,49) and to MDR (24,50,51).…”
Section: Discussionmentioning
confidence: 99%